Interaction between organic species in the formation of haloacetic acids following disinfection - Vorapot Kanokkantapong (2018)
The formation of haloacetic acids (HAAs) from the chlorination of individual and binary mixtures of organic fractions obtained from the intake of Bangkhen Water Treatment Plant in Bangkok, Thailand was investigated. Experimental results revealed that, as an individual fraction, hydrophobic base (HPOB) was the most active in forming HAAs (approx. 200 μg/mg) whereas hydrophilic acid (HPIA) was the least (approx. 40 μg/mg). In binary mixtures, acid fractions exhibited stronger inhibitory effect in forming HAAs than base fractions. With the set of experimental data obtained from this work, no relationships between specific HAA formation potential and various organic fractions concentrations in binary mixtures could be formulated. Among the various individual HAA species obtained from the chlorination of each individual organic fraction, dichloroacetic acid (DCAA) was found to be predominant. On the other hand, the chlorination of binary organic fraction mixtures often led to the formation of monochloroacetic acid (MCAA) as the predominant HAA species. Copyright © Taylor & Francis Group, LLC.